2004
DOI: 10.1080/16501960410023840
|View full text |Cite
|
Sign up to set email alerts
|

Non-surgical intervention and cost for mild traumatic brain injury: results of the who collaborating centre task force on mild traumatic brain injury

Abstract: We examined the evidence for non-surgical interventions and for economic costs for mild traumatic brain injury patients by a systematic search of the literature and a bestevidence synthesis. After screening 38,806 abstracts, we critically reviewed 45 articles on intervention and accepted 16 (36%). We reviewed 16 articles on economic costs and accepted 7 (44%). We found some evidence that early educational information can reduce long-term complaints and that this early intervention need not be intensive. Most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
93
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(101 citation statements)
references
References 24 publications
(62 reference statements)
1
93
0
3
Order By: Relevance
“…Along the health care continuum, it is likely that some of these patients then receive conflicting diagnoses by neurologist, neurosurgeons, neuro-psychologists, and psychiatrists who are using different definitions of mTBI. Given that simple early patient education has been shown to reduce long-term complaints following mTBI, the value of accurately identifying mTBI cases is clear 15,16 .…”
mentioning
confidence: 99%
“…Along the health care continuum, it is likely that some of these patients then receive conflicting diagnoses by neurologist, neurosurgeons, neuro-psychologists, and psychiatrists who are using different definitions of mTBI. Given that simple early patient education has been shown to reduce long-term complaints following mTBI, the value of accurately identifying mTBI cases is clear 15,16 .…”
mentioning
confidence: 99%
“…Ponsford et al 11 studied 202 mild TBI patients and reported that patients given an information booklet on mild TBI and coping strategies for symptoms were significantly less symptomatic at 3 months than those who were not provided education. An extensive review of articles on early intervention after mild TBI by Borg et al 58 showed that early educational information reduces long-term complaints.…”
Section: Discussionmentioning
confidence: 99%
“…Three systematic reviews reported only one clinical trial of a pharmacological intervention for concussion. [23][24][25] One study showed no effect of nasal vasopressin on cognitive symptoms secondary to mild TBI. 26 A systematic review identified studies investigating interventions initiated in the ED for short-term (one week) and medium term (one month) outcomes in adults and children who sustained mild TBI.…”
Section: Discussionmentioning
confidence: 99%